ANALISIS PENGARUH PROFITABILITAS, CASH POSITION, DEBT TO EQUITY RATIO (DER), DAN KESEMPATAN INVESTASI TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2010 – 2012 - Koapaha, Hartini Pop (JBE (Journal of Business and Economics); Volume 12 No.2, 2013 JBE UNKLAB, 2013)
The purpose of this study was to analyze the influence of Price Earning Ratio (PER), Price to Book Value Ratio (PBV), Debt to Total Equity (DER), Return on Equity (ROE), and Book Value per Share (BV) on stock returns. In addition, this study also aims to conduct advanced research for the PER, PBV, DER, ROE, and BV that is expected to prove the influence of fundamental factors may have on stock returns. The sample used is a manufacturing company listed on the Indonesia Stock Exchange in 2010-2012 . Samples were taken with a purposive sampling technique. These results indicate that the variable Price to Book Value (PBV) which have a significant effect on stock returns of manufacturing firms listed on the Indonesia Stock Exchange (BEI). While the variable Price Earning Ratio (PER), Price to Book Value Ratio (PBV), Debt to Total Equity (DER), Return on Equity (ROE), and Book Value per Share (BV) no significant effect on stock returns of manufacturing firms listed on the Indonesia Stock Exchange (BEI).